PERHITUNGAN PULLEY DAN V-BELT PADA PERANCANGAN SISTEM TRANSMISI MESIN PENCACAH ECENG GONDOK UNTUK ALTERNATIF PAKAN TERNAK - Aqsal Sheva Putra (Gorontalo Journal of Infrastructure and Science Engineering, 2022)
Water hyacinth can be an alternative feed for livestock by chopping it first so it can be easily eaten by livestock, but chopping it manually takes a very long time. The chopping machine is one solution to the problems of farmers to chop water hyacinth which can be used as an alternative animal feed. Therefore, a water hyacinth chopper is needed that is able to chop water hyacinth in large and uniform quantities. Pulley and V-Belt were chosen as the transmission system for this water hyacinth chopping machine because of several advantages, namely not making noise, relatively cheaper maintenance costs compared to gear and chain drives, while the disadvantages of using a pulley and v-belt transmission system are: the power generated is not so strong as using a transmission with gears. The method chosen to design the transmission system of the water hyacinth chopper is by measuring, observing and calculating, then analyzing the data so as to obtain an overview of the machine's performance which in turn can provide specifications for the needs of the water hyacinth chopper to be made. In the design of a water hyacinth chopping machine that uses an electric motor drive with a transmission system using a Pulley and V-belt. The size of the drive pulley is 90mm in diameter and the driven pulley has a diameter of 180 mm with ST 37 material. Then the V-belt can be obtained from the diagram according to IS:2494-1974 is a type B which has a width of 17 mm, a thickness of 11 mm and a groove angle of 38° using rubber material, the required length of the V-belt is 1333.95mm, the planned rotation is 1,400 Rpm, the V-belt axis distance is 609.23mm, the driving pulley circumference is 13.18m/s, and the required V-belt is 1 V-belt